2018
DOI: 10.2147/ijn.s176176
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of ginsenoside Re-based carbon dots applied for bioimaging and effective inhibition of cancer cells

Abstract: BackgroundFluorescent carbon-based nanomaterials have promising properties such as biosensing, cell imaging, tracing and drug delivery. However, carbon dots (CDs) with specific inherent biological functions have not been investigated. Ginsenosides are the components with multiple bioactivities found in plants of the genus Panax, which have attracted a lot of attention for their anticancer effect.Materials and methodsIn this study, we prepared a kind of novel photoluminescent CDs from ginsenoside Re by one-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…[2,3]. Owing to these properties, carbon dots (CDs) have tremendous potential to be used in a number of applications such as cell imaging and sensing [4][5][6]. Fluorescence carbon nanoparticle (CNP) shows high potential in biological labeling, bio-imaging and other different optoelectronic device application [7,8], targeted drug delivery [9,10] in cancer theranostics [11,12], and drug delivery [13].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3]. Owing to these properties, carbon dots (CDs) have tremendous potential to be used in a number of applications such as cell imaging and sensing [4][5][6]. Fluorescence carbon nanoparticle (CNP) shows high potential in biological labeling, bio-imaging and other different optoelectronic device application [7,8], targeted drug delivery [9,10] in cancer theranostics [11,12], and drug delivery [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the main reason is not clear yet, higher tolerability of non-cancerous cells, decreased or retarded cellular accumulation of CDs in healthy cells as compared to the cancerous cells have been highlighted in many recent reports to explain the enhancement of the cell proliferation of healthy cells after the CD exposure 50,81,[98][99][100] . Yao et al 101 showed that CDs specifically interact with some cellular proteins of tumor cells and downregulate the level of some proteins and the activity of enzymes that are related to tumor cell invasion ability. www.nature.com/scientificreports/ and 292.5 ± 16.36 AU (72 h) in positive control where cells were treated with H 2 O 2 (20 mM).…”
Section: Resultsmentioning
confidence: 99%
“…Although the main reason is not clear yet, higher tolerability of non-cancerous cells, decreased or retarded cellular accumulation of CDs in healthy cells as compared to the cancerous cells have been highlighted in many recent reports to explain the enhancement of the cell proliferation of healthy cells after the CD exposure 50 , 81 , 98 100 . Yao et al 101 showed that CDs specifically interact with some cellular proteins of tumor cells and downregulate the level of some proteins and the activity of enzymes that are related to tumor cell invasion ability.
Figure 4 Time-dependent changes in cell index values and the average cell index values for ( a ), ( b ) MCF7 cells, and ( c ) HDFa cells at 48 h and 72 h after the treatment with varying concentrations of CDs as compared to the negative control (medium) and positive control (water extract of Oleandrin (50 ppm).
…”
Section: Resultsmentioning
confidence: 99%
“…P. ginseng and Aconiti Lateralis Radix are widely used in traditional medicine [25] in many Asian countries such as China, Japan, India, and Korea. P. ginseng , which displays immune enhancement [26], anticancer [27], anti-inflammatory [28], and antioxidant activities [29], can increase the efficacy of Aconiti Lateralis Radix [3, 25, 30].…”
Section: Discussionmentioning
confidence: 99%